Comparação entre os efeitos da mistura gelatina-resorcina-formaldeído e do N-butil-cianoacrilato em angiorrafias de veia jugular externa de coelhos (Oryctolagus cuniculus) - Ferrigno, Cassio Ricardo Auada; Stopiglia, Ângelo João; Bechara, Gervásio Henrique [UNESP]; Futema, Fabio (Sociedade Brasileira para o Desenvolvimento da Pesquisa em Cirurgia, 2003)
PURPOSE: To compare the effects of two surgical adhesives, Colagel® and Histoacryl®, coadjutors to the classical vein suture technique, in the reinforcement of the suture line. METHODS: The procedures, conducted in 18 rabbits of the New Zealand breed, seeked to investigate the clinical evolution of the animals, as well as the evolution of healing of surgical wounds, macroscopically and microscopically. RESULTS: The results obtained showed, clinical and macroscopically, prevalence of higher inflammatory reaction in the sutures covered by Colagel® compared to the ones maintained as control and protected by Histoacryl®. CONCLUSION: There was healing delay in the surgical wounds that received Colagel® and similar results between the control group and the sutures covered by Histoacryl®.

OBJETIVO: Estudar comparativamente os efeitos de dois adesivos cirúrgicos adjutórios à técnica clássica de venorrafia, Colagel® e Histoacryl® no reforço da linha de sutura. MÉTODOS: Os procedimentos, conduzidos em 18 leporinos da raça Nova Zelândia, buscaram investigar a cicatrização de venorrafias pela evolução clínica dos animais, bem como a evolução da cicatrização das feridas cirúrgicas, macroscópica e microscopicamente. RESULTADOS: Os resultados obtidos mostraram, clínica e macroscopicamente, alterações de maior significado e, microscopicamente, predomínio de maior reação inflamatória nas suturas recobertas pelo Colagel®, comparativamente às mantidas como controle e às protegidas'' pelo Histoacryl®. CONCLUSÕES: Houve retardo na cicatrização das feridas que receberam o Colagel® e similitude de resultados entre o grupo controle e as suturas recobertas pelo Histoacryl®.
Comparison between the effects of the compound gelatin-resorsin-formaldeide and the N-butil-2-cianoacrilate in the suture of the external jugular veins in rabbits (Oryctolagus cuniculus)
Keywords: Vein suture; Rabbits; Cianoacrylate; Surgical adhesives; Venorrafias; Coelhos; Cianoacrilato; Adesivos cirúrgicos